Case report: First case report of an Emirati child with a novel gene variant causing aromatic L-amino acid decarboxylase deficiency - Babiker, Mohamed O. E.; Kurian, Manju A.; Suleiman, Jehan (Frontiers in Pediatrics, 2022)
Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare, neurometabolic disorder resulting from biallelic mutations in the dopa decarboxylase (DDC) gene. This is the first reported case of AADC deficiency in the United Arab Emirates (UAE) and describes an Emirati male patient who presented in the first few months of life with a severe phenotype of global hypotonia, developmental delay and oculogyric crisis. Following whole exome sequencing, a novel homozygous mutation in the DDC gene (c.1144G>T, p.Val382Phe) was reported and the patient underwent further testing, after which a diagnosis of AADC deficiency was confirmed. This mutation has not been previously described, but the clinical phenotype and corresponding biochemical profile confirmed that it is a pathogenic variant. The patient is currently managed at a tertiary referral center in the UAE and is treated in accordance with published guidance on AADC deficiency, including the recommended medical therapy combined with multidisciplinary care from a team of specialists. Some symptomatic improvements have been reported but at 5 years of age the patient continues to exhibit profound developmental delay, oculogyric crisis and is prone to recurrent respiratory infections. In order to improve outcomes for patients with AADC deficiency in the Middle Eastern region, there is an urgent need to raise the index of clinical suspicion, particularly among primary care physicians, pediatricians, and pediatric neurologists, and to improve access to diagnostic testing. This is particularly relevant at the current time, given the ongoing development of potentially disease-modifying gene therapy for AADC deficiency.